Self-Designed Hydrophilicity-Related Geomaterials and Their Testing Utility in Simulation of Overlying Strata Instability - Hao Zha; Weiqun Liu; Qinghong Liu (Advances in Materials Science and Engineering)
This paper mainly involved the testing of self-designed hydrophilicity-related geomaterials and application of overlying strata monitoring in a mining area in Northwest China. We employed the orthogonal testing technique to select the ingredient ratio of hydrophilicity-related geomaterials and optimized the mechanical properties of materials, such as density, elastic modulus, Poisson ratio, compressive strength, tensile strength, and water absorption rate on the basis of regression analysis. It can be seen that the proportion of the mixture clearly determines the mechanical properties of similar materials. Among them, the content of silicone oil and the cement-Vaseline ratio have the most obvious effects on the mechanical properties of the material. By using the hydrophilicity-related geomaterials with ingredient optimization, we built a physical model to simulate the failure progress of the workface in one of the coal mines in Northwest China. It was shown that three remarkable characteristic parts, including collapse zone, fissure zone, and layer-separating space, appear in the overlying strata. Furthermore, the fractured zone above the separating band is just located under the main aquifer. Finally, compared with in-field data, it was verified that the height of the collapse zone and water-guiding fissure zone measured at three boreholes are in good agreement with the experiment. Thus, the failure mode of overburden and the vertical stress and displacement changes are consistent with the actual engineering. Self-developed hydrophilicity-related geomaterials can be applied to laboratory physical simulation experiments of overlying strata. It provides the basis for future research on large-scale physical water-containing similar simulation experiments.